Mariano Fazio, Daniel Gamarra, Historia de la Filosofía. III Filosofía Moderna, Palabra, Madrid, 2002, 300 páginas - Malo Pé, Antonio (2005)
Fil: Malo Pé, Antonio. Universidad Pontificia de la Santa Cruz; Italia